Effect of citronellol on oxidative stress, neuroinflammation and autophagy pathways in an in vivo model of Parkinson's disease. Issue 11 (November 2022) - Jayaraj, Richard L.; Azimullah, Sheikh; Parekh, Khatija A.; Ojha, Shreesh K.; Beiram, Rami
Abstract: Citronellol, a monoterpene found in the essential oils of Cymbopogo plants has been reported to possess various biological properties. In the present study, we investigated the neuroprotective mechanisms of citronellol against rotenone induced neurodegeneration by using rat model of Parkinson's disease (PD). Our results demonstrated that oral administration of citronellol prevented rotenone induced reactive oxygen species production, lipid peroxidation and enhanced Nrf2 expression, catalase, glutathione peroxidase and superoxide dismutase levels in the brain. Enzyme-linked immunosorbent assays showed that citronellol reduced secretion of TNF-α, IL-1β, IL-6 and decreased MMP-9 expression levels. Further, citronellol prevented rotenone induced microglia (Iba-1 staining) and astrocyte (GFAP staining) activation. Western blot analysis showed that citronellol significantly decreased the expression of cyclooxygenase-2 and inducible nitric oxide synthase-2 that are key markers of neuroinflammation. We further evaluated the effect of citronellol on dopaminergic neurons in substantia nigra pars compacta (SNpc) and striatum (ST) which are key anatomical structures in PD. Tyrosine hydroxylase (TH) immunoreactivity showed that citronellol preserved Tyrosine hydroxylase (TH) positive dopaminergic neurons and enhanced TH striatal expression levels significantly compared to rotenone alone group. Further, to understand the effect of citronellol on apoptosis and proteotoxicity, we evaluated apoptotic markers (Bax, Bcl-2), growth regulator (mTOR) and α-synuclein expression. Citronellol attenuated rotenone induced expression of pro-apoptotic protein Bax, reduced α-synuclein expression and enhanced Bcl-2 and mTOR levels. In addition, citronellol modulated autophagy pathway by decreasing LC-3 (Microtubule-associated proteins) and p62 levels. Taken together, our results demonstrate that citronellol protected dopaminergic neurons through its antioxidant, anti-inflammatory, anti-apoptotic and autophagy modulating properties. Graphical abstract: Image 1 Abstract : Neuroprotection; Dopaminergic neurons; Citronellol; Rotenone; Apoptosis.